The relationship between the money market rates and the common stock returns: the Malaysian experience - Noor Azlan Ghazali (Penerbit Universiti Kebangsaan Malaysia, 1992)
The relationship between monetary developments and common stock returns has been the focus of a considerable amount of research in recent years. This paper addresses the relationship between the money market rates and the common stock returns in Malaysia. Statistical analyses were conducted to provide empirical linkage between the two market; i.e., money market and capital market. The results indicated that no significant relationship exist between money market rates movement and common stock returns. However, the inverse relationship between the two variables was traced in the Malaysian market. Among all money market rates, the interbank rates offer some predictive power as it is commonly used as liquidity barometer in the Malaysian inancial market. This study also found evidence of disintermediation, i.e., outlow offud from the banking sector into direct capital market due to changing level of interest rate.